IMPLEMENTASI DESAIN PEMBELAJARAN MUHADATSAH BERBASIS COMMON EUROPEAN FRAMEWORK OF REFERENCE FOR LANGUAGES (CERF) MELALUI GOOGLE CLASSROOM - Syafriansyah, Mhd; Rosalinda, Rosalinda (Center for Research and Community Service (LPPM) University of Abulyatama, 2025)
This research is motivated by research observations on the material taught in the muhadatsah course in Arabic Language Education which needs to be prepared systematically in the CERF perspective as a foreign language learning standard on the STKIP campus which has now become FKIP Alwashliyah Darussalam University Banda Aceh. This research aims to test the effectiveness of teaching materials that have been designed by previous researchers. This research aims to implement the design of muhadatsah teaching materials from the CERF perspective in Arabic language education through the Google Classroom application and its effectiveness. The method used is the Pre-experimental design method with a One group pretest-posttest design scheme with a data analysis method using the T test formula. The population is all 70 Arabic Language Education students and the sample is 15 people with research instruments using tests. The results of this research were analyzed using the T test = value (T calculated) – (T table 1%) = 8.8 - 2.977 = 5.823 (significant) and value (T calculated) – (T table 5%) = 8.8 - 2.145 = 6.655 (significant). Therefore, the conclusion shows the effectiveness of online learning media through the Google Classroom application in Arabic muhadatsah from the CERF perspective after the T test to test the validity of the values obtained so that the alternative hypothesis is accepted because the calculated t-value is greater than the t-table.